Trade costs and demand-enhancing effects of agrifood standards: Consequences for Sub-Saharan Africa - Aristide Djimgou Tchakounte; Dela-Dem Fiankor (Journal of African Trade, 2021)
Agrifood standards impede trade by increasing compliance costs, but they can also enhance trade by signalling quality. This paper disentangles the trade costs and demand-enhancing effects of two important standards-technical barriers to trade, and sanitary and phytosanitary measures-on (i) global agricultural trade flows and (ii) fruit, nut, and vegetable trade between sub-Saharan Africa and high-income OECD countries. Combining estimates fromunit value and trade value regressions set within structural gravity frameworks, we show that trading standards increase trade costs-which exporters pass on to consumers in the form of higher prices-but they also increase trade volume. For agrifood exports from sub-Saharan Africa, compliance with standards guarantees market access at higher prices to high-value OECD markets.
Keywords: F12; F14; Q17; Q18; O13; 330; Non-tariff measures; sanitary and phytosanitary measures; technical barriers to trade; sub-Saharan Africa; ad valorem equivalent; gravity model